MAPEAMENTO E CARACTERIZAÇÃO DE FERRAMENTAS DE TECNOLOGIA DA INFORMAÇÃO NA CADEIA DE SUPRIMENTOS - Marsola, Dalton Millan (2008)
Since the last years the utilization of the information technology has became a rule, especially in application like the supply chain management where the information has been the link between the companies who integrates the chain. The combination of different information technologies made it possible. Companies use the information technology in different ways, looking for the best benefit of it. The following work has the objective of mapping and characterizing the different information technologies used on the supply chain management and detects the principal sources that lead them to use this technology. The main information technology normally used in the supply chain management has been indentified and the theory model has been constructed. From the theory model developed an instrument of research of the type survey. The prove of q cochran has been used to evaluate if there are differences on the utilization of the information technology between the different types of companies and present the facts that make the companies use the information technology.(AU)